METODE MENYIKAT GIGI TEKNIK ROLL DAN SCRUB TERHADAP SKOR PLAK PASIEN PEMAKAI ORTODONTI CEKAT DI POLI GIGI RSKIA SADEWA - Belladina Yusi Lasara; Sri Ediati; Sutrisno Sutrisno (Journal of Oral Health Care, 2014)
Prevalence (number of events) composition abnormalities of the teeth in Indonesiais said to reach 80%. One way to improve these disorders is to use orthodonticappliance. Fixed orthodontic components have complex shapes that facilitate attachmentof plaque over time and may increase the risk of caries, gingivitis, andperiodontal disease is likely to occur. One of the preventive efforts made in order toavoid the problem is to control dental plaque. Among the assortment of plaque control,the most simple, safe and effective tooth brushing. Brushing effectiveness dependson several things, namely toothbrush shape, frequency, and duration of brushingyour teeth is most important is brushing technique. Election brushing technique shouldbe considered in order to achieve hygiene and oral health, especially for users offixed orthodontic. In this study, brushing technique is the technique used roll andscrub techniques because both techniques are frequently used techniques in general.The research objective was to determine the effect of method of brushing teethand roll technique to scrub plaque scores in patients wearer fixed orthodontic toothpoly RSKIA Sadewa This research is a quasi-experimental (Quasi experiment) usingdesign Pretest - posttest. Location of research in dental poly RSKIA Sadewa inBabarsari TB 16. 13, Depok, Sleman, Yogyakarta. The method used in this researchis a method of non-random sampling with sampling techniques saturation and thesample was 24 respondents. With a variable influence brushing, whereas its impactvariables plaque scores. The data was analyzed using the Wilcoxon test at the 5%significance, to determine the effect of two variables. The results showed that afterbrushing with roll technique after 2 minutes, the average plaque scores fell from 3.46to 0.73. Meanwhile, after brushing with a scrub technique, the average plaque scoresfell from 3.32 to 1.29. From the analysis of Wilcoxon on brushing techniques suggeststhat the z roll count equal to -4.287 (sig 0.002 <0.05) and the scrub brushtechnique shows that z count equal to -4.266 (sig 0.001 <0.05). There is a significanteffect between the method of brushing with roll technique to score plaques in patientswith fixed orthodontic wearers (p: 0.002) and a significant effect between method ofbrushing with a scrub technique to score plaques in patients with fixed orthodonticwearers (p: 0.001) .